The Influence of Accounting Students' Tax Understanding on Npwp Ownership Awareness Through Legal Compliance Mediation: Pengaruh Pemahaman Perpajakan Mahasiswa Akuntansi Terhadap Kesadaran Kepemilikan Npwp Melalui Mediasi Ketaatan Hukum - Kristia Armiyanti; Nurasik (Universitas Muhammadiyah Sidoarjo, 2021)
This study aims to determine prove and analyze the influence of understanding of accounting and legal observance of NPWP ownership. This study uses the Accounting Study Program Faculty of Business, Law and Social Sciences, University of Muhammadiyah Sidoarjo as its population. Samples were selected using the purposive sampling method. This research uses a quantitative approach and research data are tested using Partial Least Square (PLS) data processing. From the calculation results it is concluded that the understanding of taxation of accounting students has an influence on the awareness of NPWP ownership. Understanding of accounting students taxation has an influence on the legal compliance of accounting students. The legal compliance of accounting students has an influence on awareness of NPWP ownership. Understanding of accounting student taxation influences awareness of NPWP ownership